Enhancing the Energy‐Storage Density and Breakdown Strength in PbZrO3/Pb0.9La0.1Zr0.52Ti0.48O3‐Derived Antiferroelectric/Relaxor‐Ferroelectric Multilayers. Issue 29 (19th June 2022) - Nguyen, Minh D.; Birkhölzer, Yorick A.; Houwman, Evert P.; Koster, Gertjan; Rijnders, Guus
Abstract: Multilayer thin‐film dielectric capacitors with high energy‐storage performance and fast charge/discharge speed have significantly affected the development of miniaturized pulsed‐power devices. Here, the interfacial strain in epitaxial multilayers of antiferroelectric PbZrO3 and relaxor‐ferroelectric Pb0.9 La0.1 Zr0.52 Ti0.48 O3 is shown to significantly enhance the maximum polarization of the multilayer thin‐film capacitors, beyond that of the composing individual layers. Insights obtained from atomically resolved energy‐dispersive X‐ray spectroscopy and high‐resolution X‐ray diffraction analysis of the interface and domain structure are used to develop phenomenological models that explain the observed trends in breakdown strength and energy‐storage density as a function of multilayer period number. The underlying mechanism is the mechanical coupling between the layers that depends on the individual layer thicknesses. These factors result in a strongly enhanced recoverable energy‐storage density (increased by a factor of 4 to ≈128.4 J cm −3 ) with high efficiency (≈81.2%). Moreover, the multilayer films show almost fatigue‐free energy‐storage performance after 10 10 switching cycles, even at elevated temperatures up to 220 °C, demonstrating their robustness. The outstanding properties show the great potential of epitaxial multilayers for energy‐storage applications, due to the well‐defined separate layers and coupling of properties across the interfaces, not present in ceramic composites. Abstract : Record‐high energy‐storage density of 128.4 J cm −3 and energy efficiency of 81.2% are simultaneously achieved in [PL/PZ] N = 8 multilayer films based on alternating relaxor‐ferroelectric and antiferroelectric layers. The impact of the interfacial layer on polarization and breakdown strength of the multilayer films is investigated by means of high‐resolution X‐ray diffraction and atomically resolved energy‐dispersive X‐ray spectroscopy.